Risk factors and prognostic significance of anemia in children with HIV infection on antiretroviral therapy. (1st December 2022) - Lubega, Joseph; Grimes, Amanda; Airewele, Gladstone; Bulsara, Shaun; Kim, Taylor Olmsted; Haq, Heather; Peckham-Gregory, Erin; Wanless, Sebastian R.; Elyanu, Peter; Musoke, Philippa; Lumumba, Mwita; Kekitiinwa, Adeodata; et al.
Abstract : Objectives: To establish the incidence, risk factors and prognostic effect of anemia in children living with HIV (CLWH). Design: Retrospective nested case–control study of patients 0–18 years in five centers in sub-Saharan Africa, 2004–2014. Methods: Incident cases of anemia were identified from electronic records and matched with CLWH without anemia. We calculated the incidence density of anemia and used conditional logistic regression to evaluate its association with risk factors, stratified by severity and type of anemia. We used a Cox proportional hazards model to evaluate the impact of anemia on survival. Results: Two thousand, one hundred and thirty-seven children were sampled. The incidence density of anemia was 1 per 6.6 CLWH-years. Anemia was moderate in 31.8% and severe in 17.3% of anemia cases, which had 10-year mortality hazards of 3.4 and 4.5, respectively. Microcytic anemia (36% cases) was associated with 2.3-fold hazard of 10-year mortality, and with malnutrition and CD4 + suppression. Normocytic anemia (50.5% cases) was associated with 2.6-fold hazards of 10-year mortality, and with more severe malnutrition, CD4 + suppression, and WHO stage, but inversely associated with lamivudine and nevirapine therapy. Macrocytic anemia (13.5% cases) was neither associated with higher 10-year mortality nor with severe malnutrition or CD4 + suppression but was associated with WHO stage II/III and negatively associated with lamivudine therapy. Conclusion: This large multicountry study of CLWH found a high incidence density of anemia. Higher severity, normocytic and microcytic types of anemia were independently associated with long-term mortality. Laboratory studies are needed to decipher the mechanisms of anemia and how it impacts mortality in CLWH.